2006
DOI: 10.1042/bst0340774
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient regulation of pancreatic β-cell function in diabetes: problems and potential solutions

Abstract: Increasing prevalence of obesity combined with longevity will produce an epidemic of Type 2 (non-insulin-dependent) diabetes in the next 20 years. This disease is associated with defects in insulin secretion, specifically abnormalities of insulin secretory kinetics and pancreatic beta-cell glucose responsiveness. Mechanisms underlying beta-cell dysfunction include glucose toxicity, lipotoxicity and beta-cell hyperactivity. Defects at various sites in beta-cell signal transduction pathways contribute, but no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that GLP-1 concentration in serum is increased in normal weight people after a meal, but not in morbidly obese patients [79]. Furthermore, GLP-1 has been also shown to promote satiety and decrease energy intake through its interaction with its receptors in the brain [80,81]. In a study by Pereferrer et al, baseline GLP-1 levels in non-obese rats were lower than those of obese animals, while its levels post-sleeve gastrectomy in obese rats have been shown to be lower than pre-interventional levels [82].…”
Section: Gastric Emptyingmentioning
confidence: 97%
“…It has been demonstrated that GLP-1 concentration in serum is increased in normal weight people after a meal, but not in morbidly obese patients [79]. Furthermore, GLP-1 has been also shown to promote satiety and decrease energy intake through its interaction with its receptors in the brain [80,81]. In a study by Pereferrer et al, baseline GLP-1 levels in non-obese rats were lower than those of obese animals, while its levels post-sleeve gastrectomy in obese rats have been shown to be lower than pre-interventional levels [82].…”
Section: Gastric Emptyingmentioning
confidence: 97%
“…No single lesion can account for MS or its associated diseases [St. Pierre et al, 2005;Flatt and Green, 2006]. However, gene expression studies have shown that there is a coordinate reduction in oxidative gene activities along with increased expression of several other genes in type 2 diabetes [Vechoor et al, 2002].…”
Section: Oxidative Stress Mitochondrial Damage and Type 2 Diabetesmentioning
confidence: 99%
“…In contrast, the mutant enzyme was significantly less stable compared with wild-type CEL. A (35,36). Furthermore, it was shown to stimulate ␤-cell neogenesis, growth, and differentiation in rodents and tissue culture and to inhibit ␤-cell apoptosis in vitro.…”
Section: Diabetes and Pancreatic Exocrine Dysfunction Due To Mutationmentioning
confidence: 99%